Odpowiedź
Fałsz
n = 1, wielomian jest x
n = 2, wielomian jest x(x-1)
n = 3, wielomian jest x(x-1)(x-2)
n = 4, wielomian jest x(x-1)(x-2)(x-3)
n = 5, wielomian jest x(x-1)(x-2)(x-3)(x-4)
[tex]x^5 - 10 x^4 + 35 x^3 - 50 x^2 + 24 x[/tex]
[tex]\displaystyle \left( {{n} \atop {5}} \right) = \left( {{5} \atop {5}} \right) = 1[/tex]
zgadza się
n = 6, wielomian jest x(x-1)(x-2)(x-3)(x-4)(x-5)
[tex]x^6 - 15 x^5 + 85 x^4 - 225 x^3 + 274 x^2 - 120 x[/tex]
[tex]\displaystyle \left( {{n} \atop {5}} \right) = \left( {{6} \atop {5}} \right) = 6[/tex]
nie zgadza się
n = 7, wielomian jest x(x-1)(x-2)(x-3)(x-4)(x-5)(x-6)
[tex]x^7 - 21 x^6 + 175 x^5 - 735 x^4 + 1624 x^3 - 1764 x^2 + 720 x[/tex]
[tex]\displaystyle \left( {{n} \atop {5}} \right) = \left( {{7} \atop {5}} \right) = \dfrac {7!} { \: 5! \cdot (7-5)! \: } = \dfrac {7!} { \: 5! \cdot 2! \: } = \dfrac { \: 5! \cdot 6 \cdot 7 \: } { \: 5! \cdot 2! \: } = \dfrac { \: 6 \cdot 7 \: } { 2! } = 21[/tex]
nie zgadza się
Szczegółowe wyjaśnienie
Dowód przez pokazanie kontrprzykładu.